DEVELOPMENT OF INTERNET-BASED ARABIC LEARNING MEDIA AT MADRASAH ALIYAH DARUL HAKIM OLD MOUNTAIN PADANG LAWAS NORTH - Harahap, Shinta Zumana; Zainuddin, Darwin (Academy of Education Journal, 2023)
The purpose of this study was to analyze the Development of Internet-Based Arabic Learning Media at Madrasah Aliyah Darul Hakim Gunung Tua Padang Lawas Utara. This type of research is qualitative research which describes data using a series of sentences. The nature of the research to be carried out by researchers is descriptive in nature, namely research that describes in detail about an object under study. This research refers to data sources collected from direct visits to research objects, in this case homeroom teachers and students, as well as secondary data obtained through library research. This study uses a combination of technical triangulation and source triangulation to test the validity of the data and analyze data based on data sources. From this study it is known that the Development of Internet-Based Arabic Learning Media at Madrasa Aliyah Darul Hakim Gunung Tua Padang Lawas Utara is still conventional, namely the learning process in which the material is described by the teacher using learning media that is less interesting or without learning media then gives assignments to students with limited material and books, so that many students do not achieve completeness in the competencies being taught. Practicality is obtained based on the results of the teacher's and student's assessment of learning media, where the average teacher's assessment of the media is in the very practical category and the average student's assessment of the media is in the very practical category. Effectiveness is obtained based on the results of observations of teacher activity on the use of learning media, where the average assessment of teacher activity on media use is in the very effective category